Biomechanical analysis of ankle ligamentous sprain injury cases from televised basketball games: Understanding when, how and why ligament failure occurs - Panagiotakis,E; Mok,K-M; Fong,DT-P; Bull,AMJ (Journal of Science and Medicine in Sport, 2017)
OBJECTIVES: Ankle sprains due to landing on an opponent's foot are common in basketball. There is no analysis to date that provides a quantification of this injury mechanism. The aim of this study was to quantify the kinematics of this specific injury mechanism and relate this to lateral ankle ligament biomechanics. DESIGN: Case series. METHODS: The model-based image-matching technique was used to quantify calcaneo-fibular-talar kinematics during four ankle inversion sprain injury incidents in televised NBA basketball games. The four incidents follow the same injury pattern in which the players of interest step onto an opponent's foot with significant inversion and a diagnosed ankle injury. A geometric analysis was performed to calculate the in vivo ligament strains and strain rates for the anterior talofibular ligament (ATFL) and the calcaneofibular ligament (CFL). RESULTS: Despite the controlled selection of cases, the results show that there are two distinct injury mechanisms: sudden inversion and internal rotation with low levels of plantarflexion; and a similar mechanism without internal rotation. The first of these mechanisms results in high ATFL and CFL strains, whereas the second of these strains the CFL in isolation. CONCLUSIONS: The injury mechanism combined with measures of the ligament injury in terms of percentage of strain to failure correlate directly with the severity of the injury quantified by return-to-sport. The opportunity to control excessive internal rotation through proprioceptive training and/or prophylactic footwear or bracing could be utilised to reduce the severity of common ankle injuries in basketball.